KARAKTERISASI BAKTERI PATOGEN PENYEBAB LAYU PADA TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Fuji Arriani, Intan; Latief Abadi, Abdul; Qurata Aini, Luqman (Universitas Islam Balitar, 2020)
Shallot (Allium ascalonicum L.) is one of the vegetable commodities in the form of tubers that have a high economic value. The development of shallot cultivation in Indonesia often experiences obstacles, one of which is an obstacle in the process of shallot cultivation, namely the attack of Plant Disturbing Organisms (OPT). Information about diseases caused by pathogenic bacteria is still very limited. This study aims to determine the symptoms and identification of pathogenic bacteria that cause wilt in shallots. Bacterial isolation was carried out using Nutrient Agar (NA) media and 36 bacterial isolates were collected from shallots. Bacterial isolates were then tested for pathogenicity to determine the ability of bacteria to cause wilt disease in shallots. The results of isolation obtained 10 bacterial isolates that can show symptoms on red onions namely wilted leaves, yellow and soft rotten tubers. Four isolates including positive can show hypersensitivity symptoms, namely M11, N20, N17 and N14. Based on the identification of bacteria in physiology showed 2 groups of different isolates. Biochemical test results of Isolate M11, N20 and show species suspected of B. cepacia. N3 and N14 isolates are suspected to be E. carotavora subsp. carotavora. The bacterial isolates N7, N17, P5 and P7 were suspected to be E. carotavora subsp. betavasculorum. The isolate of N4 bacteria is suspected to be E. cacticida.